Tympanoplasty with Boomerang-Shaped Chondoperichondrial Graft: Long-Term Results - Yağcı, Tarık; Dundar, Rıza; Yükkaldıran, Ahmet (ENT Updates, 2022)
Background: we aimed in this study to evaluate and present the long-term results of type 1 tympanoplasty patients who were operated by using boomerang-shaped chon- droperichondrial graft. Methods: One hundred thirty-eight patients who underwent primary type 1 tympano- plasty, had tragal cartilage removal, and used boomerang-shaped chondroperichon- drial graft between September 2010 and March 2014 were examined and 62 patients who could be reached through their contact information and had complete preopera- tive records were included in this retrospective study. Audiological and otomicroscopicexaminations were performed on the patients who were contacted. The condition of the graft, preoperative and postoperative air-bone gap values, and retraction find-ings on graft were noted. These findings were compared with preoperative notes. Results: The preoperative mean air-bone gap value of the patients was 23.690±1.036 decibels. As a result of the audiological examination performed at the last fol-low-up of these patients, the mean air-bone gap values of at least fifth year post- operatively were measured as 10.6±0.791 decibels (P < .0001). The control periodswere between 122 and 60 months and the mean control period was 73.03 months. Perforation was detected in 6 (9.7%) patients on otomicroscopic examination. Conclusion: Considering the long-term results, we think that this grafting technique of tympanoplasty has adequate and satisfactory results.